Political giving : making sense of individual campaign contributions - Johnson, Bertram N. (FirstForumPress, onc., 2013)
Why do some 30 million people in the United States give money to political candidates and causes--even though most individual contributions are irrational from the perspective of a strict cost-benefit analysis? How do campaign fundraisers tap into potential donors' motivations? Exploring three decades of historical data and also drawing extensively on the insights of contemporary campaign directors and consultants, Bertram Johnson makes sense of why people give and considers what this means for the campaign finance system, and the quality of representation, in the United States.